INDONESIAN DIPLOMACY TO SUPPORT DIGITAL TRANSFORMATION THROUGH THE 2022 G20 SUMMIT - Salsa Nabila Rifky; Nurfitri Nugrahaningsih; Dewi Suratiningsih (Sean Institute, 2023)
The research aims to provide an explanation regarding how diplomacy is carried out by Indonesia to support digital transformation through the 2022 G20 Summit. This research entitled